Permasalahan Implementasi Akuntansi Syari’ah pada Lembaga Keuangan Syari’ah di Indonesia - Arjun Ferandika; Depi Putri Erlia; Listia Nur Wahida; Yasmin Darmawan Nusa; Esty Apridasari (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze the problems in the implementation of Islamic accounting in Islamic financial institutions in Indonesia, particularly those related to human resource (HR) understanding of Sharia principles and contracts. This research employs a qualitative method with a literature study approach. Data were obtained from various secondary sources such as books, scientific journals, and previous studies related to Islamic accounting. The data collection technique was carried out by reviewing and analyzing relevant literature. Data analysis was conducted descriptively to understand the issues in the implementation of Islamic accounting. The results of the study indicate that one of the main problems in implementing Islamic accounting is the lack of HR understanding of contract concepts such as murabahah, mudharabah, musyarakah, and ijarah, so that in practice they are often treated similarly to conventional accounting systems. In addition, limited training, low Islamic financial literacy, and the suboptimal implementation of Islamic accounting standards such as PSAK Syariah also pose challenges in the application of Islamic accounting. Therefore, efforts are needed to improve the quality of human resources through education, training, certification, as well as strengthening regulations and supervisory systems so that the implementation of Islamic accounting can run optimally and in accordance with Sharia principles